Effect of diet on body composition and performance parameters - VO2max, HR and power, among young football players - Mizera, Krzysztof Maciej (Journal of Education, Health and Sport, 2023)
Nutrition acts an important role for soccer players as it provides energy and affects recovery after training. Objective: The aim of the study was to assess the method and quality of nutrition of young football players and the impact of nutrition on VO2max, power, heart rate and somatic parameters. Results: The obtained results indicate that with the increase in calories and nutrients, the percentage of water in the body decreases. In other cases, increasing the amount of calories consumed is associated with an increase in BMI, fat content, lean body mass and muscle mass. VO2max did not correlate with any of the dietary parameters as did the number of breaths per minute. Heart rate results in most cases, when correlated with dietary parameters, produce an inversely proportional fit. Resting heart rate (HR) correlates with eight of the eleven deictic parameters, giving a level of compliance in the range of -0.48 to -0.73. In the case of the size of the change in heart rate after exercise, its size is greater the more calories and nutrients are consumed by the test subjects. These correlations are then proportional. These results range from 0.52 to 0.75. Conclusion: It is not the amount of calories consumed, but mainly carbohydrates that influence the weight of soccer players. On the other hand, the amount of calories and proteins consumed have an impact on the maximum power generated by players. The diet used by the players does not affect their VO2max and the number of breaths per minute, and the amount of calories and carbohydrates consumed affects the recovery time of the circulatory system (heart rate decrease) immediately after exercise.